Nodal asymmetry and hedgehog signaling during vertebrate left–right symmetry breaking - Negretti, Maria Isabella; Böse, Nina; Petri, Natalia; Kremnyov, Stanislav; Tsikolia, Nikoloz (Frontiers in Cell and Developmental Biology, 2022)
Development of visceral left-right asymmetry in bilateria is based on initial symmetry breaking followed by subsequent asymmetric molecular patterning. An important step is a left-sided expression of transcription factor pitx2 which is mediated by asymmetric expression of the nodal morphogen in the left lateral plate mesoderm of vertebrates. Processes leading to the emergence of the asymmetric nodal domain differ depending on mode of symmetry breaking. In Xenopus laevis and mouse embryos the leftward fluid flow on the ventral surface of the left-right organizer leads through intermediate steps to enhanced activity of the nodal protein on the left side of the organizer and subsequent asymmetric nodal induction in the LPM. In the chick embryo the asymmetric morphogenesis of the axial organs leads to paraxial nodal asymmetry during late gastrulation stage. Although it was shown that hedgehog signalling is required for initiation of the nodal expression, the mechanism of the induction of the nodal asymmetry remains to be clarified. In this study we established activation of hedgehog signalling in early chick embryo to study further its role in initiation of asymmetric nodal expression. Our data reveals that hedgehog signalling is not only required but is also sufficient to induce the nodal expression in competent domains of chick embryo while treatment of Xenopus embryos led to moderate nodal inhibition. We discuss the role of the symmetry breaking and competence in initiation of asymmetric gene expression.